Hasil analisis sefalometri metode holdaway pasien ortodonti usia 19-26 tahun di rsgm – p fkg usakti - Ayunda Adelia; Yuniar Zen (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Malocclusion is a discrepancy in the relationship between the jaw and tooth that deviates from normal. To fix the malocclusion problem in the oral cavity, orthodontic treatment can be used in performed. Cephalometric analysis can be used in determining the diagnosis and treatment plan. One of the analysis is the Holdaway method. Holdaway analysis is considered as a more precise method, making it easier for researchers analysis in orthodontic patients to assess facial soft tissue and facial hard tissue structures effectively because it has 11 parameters; facial angle, nose tip distance, superior labial sulcus depth, inferior labial sulcus depth, upper lip curvature, upper lip distance, chin thickness, upper lip thickness, upper lip curvature, upper lip strain, H angle and skeletal curvature. Purpose: To determine the results of cephalometric analysis in adult orthodontic patients aged 19-26 years at RSGM-P FKG Usakti with Holdaway analysis. Methods: A descriptive observational study with a cross-sectional design, and selection of cephalograms by purposive sampling in adult orthodontic patients at RSGM-P FKG Usakti in 2021-2022. Results: The average patient's facial angle was 89⁰, the average distance from the apex of the nose was 2,5mm, the mean superior labial sulcus depth was 7,82mm, the mean labial sulcus depth inferior 4,3mm, mean Li-H distance of 1,30mm, mean thickness of the chin 12,6mm, average thickness of the upper lip 12,6, mean Sn-H 5mm, mean upper lip strain of 11,70mm, mean skeletal convexity of 3,4mm, and mean angle H 16.15⁰. Conclusion: Overview of cephalometric analysis in orthodontic patients with Holdaway analysis shows that the patient has a facial profile with facial angle, H angle and convex skeletal convexity, small nasal tip distance, superior labial sulcus depth, inferior labial sulcus depth and less chin thickness ideal, upper lip curvature and less than ideal upper lip strain, and ideal Li to H distance